PENGARUH TOR-TOR HATA SOPISIK TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK PERTIWI SETDA PROVINSI KOTA PEKANBARU - Sitinjak, Suyanti; Zulkifli, Zulkifli; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to know the influence of Tor-tor Hata Sopisik against the psychomotor skills of children aged 5-6 years in Pertiwi Setda Province Pekanbaru City Kindergarten. The research used experimental method with one group pre-test post-test design design. The samples used in this study were 15 students. The data collection technique used is observation. Technique of data analysis using t-test testing by using program of SPSS 16.0 The research hypothesis that there is influence of activity of Tor-tor Hata Sopisik to psychomotor ability child aged 5-6 years in Pertiwi Setda Province Pekanbaru City Kindergarten. Based on data analysis known tarithmetic = 13,485> ttable = 2,145 withSig. (2-tailed) = 0.000. Because of Sig <0,05 it can be concluded that there is a difference of psychomotor ability before and after dance Tor-tor Hata Sopisik. It can be interpreted that there is influence Tor-tor hata sopisik to psychomotor skills of children aged 5-6 years in Pertiwi Setda Province Pekanbaru City Kindergarten significant that is equal to 22.66%.Keyword: The Ability of Psychomotor, The Activity of Tor-tor Hata Sopisik